SWEARWORDS USED IN DETECTED MOVIE VIEWED BY SPEECH ACT THEORY - Rullyanti, Merry; Devita, Fenti (JURNAL SMART, 2017)
Abstract This thesis examines the swearwords using the speech act theory in Accepted movie directed by Steve Pink. The objectives of this research are; (1) To find kinds of swearwords used by the characters. (2) To classify the speech act categories used by the characters when they uttered the swearwords. (3) To investigate the contexts of swearing. The dominant kind of speech act in the swearwords that the characters use is expressive because Americans get used to express their feelings spontaneously. The most dominant context that appeared is dysphemistic context that makes the movie more interesting with the creative metaphors. Keywords: Swearwords, Speech Act, Accepted